Perencanaan Model PBL dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran PAI - Riski Karlina; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2023)
In the 21st century, there are many challenges faced by teachers and students in the world of education, especially in the learning aspect. Where the teacher serves as a facilitator for students in order to train students' critical thinking skills. While students are required to be able to hone their critical thinking skills so that they are able to deal with problems that occur in their lives, both in the present and in the future. Efforts can be made by teachers in honing students' critical thinking skills are one of them by applying the PBL model. This study aims to find out how to plan the PBL model on the material Faith in Qada and Qadar at SMA Negeri 7 Padang. The method used in this research is a qualitative method with a case study type. The data sources for this study were Islamic Religious Education teachers, curriculum representatives, and 5 students of class XII IPA 6 SMA Negeri 7 Padang. The instruments used were interview guidelines and observation guidelines. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the planning of the Problem-Based Learning (PBL) model in the subject of Islamic Religious Education in improving students' critical thinking skills on the subject of Faith in Qada and Qadar at SMA Negeri 7 Padang is guided by the syllabus and lesson plans and where it can be seen that students fulfill the indicators critical thinking in the learning process using the PBL model.